How Do Emergency Medicine Residency Programs Structure Their Clinical Competency Committees? A Survey. (16th October 2015) - Doty, Christopher I.; Roppolo, Lynn P.; Asher, Shellie; Seamon, Jason P.; Bhat, Rahul; Taft, Stephanie; Graham, Autumn; Willis, James
Abstract: Background: The Accreditation Council for Graduate Medical Education (ACGME) recently has mandated the formation of a clinical competency committee (CCC) to evaluate residents across the newly defined milestone continuum. The ACGME has been nonproscriptive of how these CCCs are to be structured in order to provide flexibility to the programs. Objectives: No best practices for the formation of CCCs currently exist. We seek to determine common structures of CCCs recently formed in the Council of Emergency Medicine Residency Directors (CORD) member programs and identify unique structures that have been developed. Methods: In this descriptive study, an 18‐question survey was distributed via the CORD listserv in the late fall of 2013. Each member program was asked questions about the structure of its CCC. These responses were analyzed with simple descriptive statistics. Results: A total of 116 of the 160 programs responded, giving a 73% response rate. Of responders, most (71.6%) CCCs are chaired by the associate or assistant program director, while a small number (14.7%) are chaired by a core faculty member. Program directors (PDs) chair 12.1% of CCCs. Most CCCs are attended by the PD (85.3%) and selected core faculty members (78.5%), leaving the remaining committees attended by any core faculty. Voting members of the CCC consist of the residency leadership either with the PD (53.9%) or without the PD (36.5%) as a voting member. CCCs have an average attendance of 7.4 members with a range of three to 15 members. Of respondents, 53.1% of CCCs meet quarterly while 37% meet monthly. The majority of programs (76.4%) report a system to match residents with a faculty mentor or advisor. Of respondents, 36% include the resident's faculty mentor or advisor to discuss a particular resident. Milestone summaries (determination of level for each milestone) are the primary focus of discussion (93.8%), utilizing multiple sources of information. Conclusions: The substantial variability and diversity found in our CORD survey of CCC structure and function suggest that there are myriad strategies that residency programs can use to match individual program needs and resources to requirements of the ACGME. Identifying a single protocol for CCC structure and development may prove challenging.